A review on ethnobotany, phytochemistry, and pharmacology of the genus Duhaldea DC - Shu, Liangyin; Li, Kailin; Yang, Suyu; Hu, Mengdie; Ming, Xinrong; Yan, Bingyuan; Guan, Liangjun; Xiao, Shunli (Frontiers in Pharmacology, 2024)
The botanical drugs of genus Duhaldea DC. have been traditionally utilized in folk medicine for the treatment of a wide array of illnesses, encompassing fractures, bone wounds, carbuncles and poisoning, bronchitis, bruises, giddy with hypertension of qi, and lung deficiency cough. The genus Duhaldea DC. comprises 15 species widespread in Central, East, and Southeast Asia and 7 species (2 endemic) in China. The review aims to provide a systematic overview of ethnopharmacology, phytochemistry, and pharmacology of Duhaldea DC. and to explore the future therapeutic potential and scientific potential of this genus. The data were systematically collected from books and scientific databases such as PubMed, Web of Science, Google Scholar, CNKI, and doctoral and master’s theses. To date, a total of 352 metabolites have been isolated from this genus, and terpenoids, flavonoids, phenylpropanoids, and inositol angelates are the primary contributors to the pharmacological activities of Duhaldea DC. The crude extracts and isolated phytochemical metabolites from this genus have been shown to exhibit various pharmacological activities, including anti-inflammatory, antimicrobial, anti-osteoporotic, anticancer, and antioxidant activities. Despite notable advancements in our understanding of the chemical constituents and pharmacological properties of Duhaldea DC., it is absolutely crucial to conduct additional research into the pharmacology and toxicology of these species to definitively ascertain their safety, efficacy, and quality.